2015
DOI: 10.1101/gad.270611.115
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for substrate recognition by the human N-terminal methyltransferase 1

Abstract: α-N-terminal methylation represents a highly conserved and prevalent post-translational modification, yet its biological function has remained largely speculative. The recent discovery of α-N-terminal methyltransferase 1 (NTMT1) and its physiological substrates propels the elucidation of a general role of α-N-terminal methylation in mediating DNA-binding ability of the modified proteins. The phenotypes, observed from both NTMT1 knockdown in breast cancer cell lines and knockout mouse models, suggest the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(136 citation statements)
references
References 25 publications
6
130
0
Order By: Relevance
“…24 To explore a new scaffold, we initiated our efforts to design a series of SAM–peptide conjugates by linking a SAM analog with peptides that start with either Ala or Gly through an alkyl group as our model system. Our crystal structure suggested that the distance between the sulfonium ion and the α- N -terminal nitrogen atom is 4.7 Å 30 And for most protein methyltransferases, this distance varies from 2.2 Å to 4.7 Å 2933 Hence, we chose an ethylene or a propylene group as a linker and designed a series of compounds 1a–f targeting NTMT1 with substrate peptides that start with GPK/R. 34,35 We also designed compounds 1g–j by adding either an Ala or Gly to an ethylene group to extend the linker length for two peptide substrates PPKR and SPKR to probe an optimal linker.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…24 To explore a new scaffold, we initiated our efforts to design a series of SAM–peptide conjugates by linking a SAM analog with peptides that start with either Ala or Gly through an alkyl group as our model system. Our crystal structure suggested that the distance between the sulfonium ion and the α- N -terminal nitrogen atom is 4.7 Å 30 And for most protein methyltransferases, this distance varies from 2.2 Å to 4.7 Å 2933 Hence, we chose an ethylene or a propylene group as a linker and designed a series of compounds 1a–f targeting NTMT1 with substrate peptides that start with GPK/R. 34,35 We also designed compounds 1g–j by adding either an Ala or Gly to an ethylene group to extend the linker length for two peptide substrates PPKR and SPKR to probe an optimal linker.…”
mentioning
confidence: 85%
“…29,30 So far, there is only one specific inhibitor available for this enzyme, which was synthesized through a click chemistry and reported by our laboratory. 24 To explore a new scaffold, we initiated our efforts to design a series of SAM–peptide conjugates by linking a SAM analog with peptides that start with either Ala or Gly through an alkyl group as our model system.…”
mentioning
confidence: 99%
“…METTL11B was suggested to be primarily a monomethyltransferase that may prime substrates for the action of NTMT1 (55). Crystal structures of human NTMT1 in complex with substrate peptides have been solved (56,57) that support the substrate specificity of this enzyme determined from kinetic (58,59) and inhibitor studies (60). A variety of functions have been proposed for XPK N-terminal methylation of eukaryotic proteins (61), including regulating the affinity of protein binding to DNA (62,63), DNA repair (64-66) and protection from aminopeptidase attack (49).…”
Section: Protein N-terminal Methyltransferasesmentioning
confidence: 99%
“…This homologue was suggested as another NTMT in 2010 and confirmed to be an NTMT by 2013 . Both NTMT1 and NTMT2 recognize an X‐P‐K/R consensus sequence, in which X can be any amino acid, except D or E . Although NTMT2 was originally proposed to be a monomethylase, recent studies indicated that it could also fully methylate both GPKRIA and PPKRIA peptides .…”
Section: Discovery Of Protein Ntmtsmentioning
confidence: 99%
“…The discovery of NTMT1/NRMT1 has led to rising reports on N‐terminal methylation existing in tumor suppressor retinoblastoma 1 (RB1), oncoprotein SET (also known as I2PP2A, TAF1α), damaged DNA‐binding protein 2 (DDB2), poly(ADP‐ribose) polymerase 3 (PARP3), and centromere proteins A and B (CENP‐A&B, Figure ) . Crystal structures of NTMT1 in complex with peptide substrates and SAH revealed the structural basis for the preferred recognition motif X‐P‐K/R (X can be any amino acid, except D or E) . Substrate recognition is discussed in more detail in Section 2.4.…”
Section: Discovery Of Protein Ntmtsmentioning
confidence: 99%